1996
DOI: 10.1111/j.1600-0838.1996.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude and timing of electromyographic activity during sprinting

Abstract: Amplitude and timing of electromyographic activity during sprinting. Scand J Med Sci Sports 1996: 6: 15-21. 0 Munksgaard, 1996 The aim of this study was to make descriptive analyses of the muscle activities in the lower extremity during maximal sprinting. Nine healthy sprinters were examined during maximal sprinting using telemetric electromyography (EMG). Seven muscles of the lower extremities were investigated: biceps femoris, medial hamstrings (semimembranosus and semitendinosus), rectus femoris, gluteus ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 11 publications
6
48
0
2
Order By: Relevance
“…As suggested (McLay et al, 1990), the most likely function of swing-side contractions of the GM is to decelerate the leg during swing phase. These results are also consistent with those reported by previous studies (Mann and Hagy, 1980b; Montgomery et al, 1984;Nilsson et al, 1985;Jonhagen et al, 1996). While this hypothesis is difficult to test, it is consistent with data on both the timing and magnitude of normalized GM contractions at different speeds.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…As suggested (McLay et al, 1990), the most likely function of swing-side contractions of the GM is to decelerate the leg during swing phase. These results are also consistent with those reported by previous studies (Mann and Hagy, 1980b; Montgomery et al, 1984;Nilsson et al, 1985;Jonhagen et al, 1996). While this hypothesis is difficult to test, it is consistent with data on both the timing and magnitude of normalized GM contractions at different speeds.…”
Section: Discussionsupporting
confidence: 83%
“…One of these functions may be to help actively extend the thigh during stance (Hypothesis 4). In particular, the timing and magnitude of stance-side GM contractions were very similar to those of the hamstrings during both walking and running, confirming the results of several previous studies (Mann and Hagy, 1980b;Montgomery et al, 1984;Nilsson et al, 1985;Jonhagen et al, 1996). Such results are particularly interesting in terms of uphill locomotion.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…11,27 In this case report, preintervention EMG recordings of the hamstrings during terminal swing and the first half of the stance phase of running revealed average levels of hamstring activity (48.1% MVIC), well above what is considered normal for running. Based on EMG recordings, Pinnington et al 25 reported the average hamstring activity during terminal swing and the first half of the stance phase of running to be 19% MVIC.…”
Section: Bergeronmentioning
confidence: 99%
“…Submaximal contractions are used in everyday life, but high-force eccentric (lengthening) contractions, such as in the hamstring muscles during sprinting, are associated with muscle damage and pain [18,27,37]. The majority of hamstring musculotendinous injuries occur during maximum sprinting when braking knee extension or at foot strike [7], whereas most proximal hamstring avulsions occur during forced hip flexion and knee extension, such as with a fall during waterskiing [9,20]. In one kinematic and electromyographic study late swing phase Each author certifies that he or she has no commercial associations (eg, consultancies, stock ownership, equity interest, patent/licensing arrangements, etc) that might pose a conflict of interest in connection with the submitted article.…”
Section: Introductionmentioning
confidence: 99%